(untitled) (Bangladesh Journal of Medical Science, 2011)
An orbital abscess is a rare complication of an odontogenic infection, but it can lead to high morbidity and mortality. This paper presents a case of orbital abscess secondary to an infection of upper molar teeth that developed after the tooth extraction. The direct spread of the infection through the oroantral fistula and extended to the orbit close to the superior orbital fissure. Keywords: Abscess; orbital complication; sinusitis; odontogenic. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7811 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.137-140